Rapid and Sensitive Detection of Bartonella bacilliformis in Experimentally Infected Sand Flies by Loop-Mediated Isothermal Amplification (LAMP) of the Pap31 Gene - Nasikarn Angkasekwinai (2018)
© 2014. Carrion' disease, caused by Bartonella bacilliformis, remains truly neglected due to its focal geographical nature. A wide spectrum of clinical manifestations, including asymptomatic bacteremia, and lack of a sensitive diagnostic test can potentially lead to a spread of the disease into non-endemic regions where competent sand fly vectors may be present. A reliable test capable of detecting B. bacilliformis is urgently needed. Our objective is to develop a loop-mediated isothermal amplification (LAMP) assay targeting the pap31 gene to detect B. bacilliformis. The sensitivity of the LAMP was evaluated in comparison to qPCR using plasmid DNA containing the target gene and genomic DNA in the absence and presence of human or sand fly DNA. The detection limit of LAMP was 1 to 10 copies/µL, depending on the sample metrics. No cross-reaction was observed when testing against a panel of various closely related bacteria. The utility of the LAMP was further compared to qPCR by the examination of 74 Lutzomyia longipalpis sand flies artificially fed on blood spiked with B. bacilliformis and harvested at days (D) 1, 3, 5, 7 and 9 post feeding. Only 86% of sand flies at D1 and 63% of flies at D3 were positive by qPCR. LAMP was able to detect B. bacilliformis in all those flies confirmed positive by qPCR. However, none of the flies after D3 were positive by either LAMP or qPCR. In addition to demonstrating the sensitivity of the LAMP assay, these results suggest that B. bacilliformis cannot propagate in artificially fed L. longipalpis. The LAMP assay is as sensitive as qPCR for the detection of B. bacilliformis and could be useful to support diagnosis of patients in low-resource settings and also to identify B. bacilliformis in the sand fly vector.